DNA-Unwinding Dynamics of Escherichia coli UvrD Lacking the C-Terminal 40 Amino Acids - Yokota, Hiroaki (Biophys J, 2020)
The E. coli UvrD protein is a nonhexameric DNA helicase that belongs to superfamily I and plays a crucial role in both nucleotide excision repair and methyl-directed mismatch repair. Previous data suggested that wild-type UvrD has optimal activity in its oligomeric form. However, crystal structures of the UvrD-DNA complex were only resolved for monomeric UvrD, using a UvrD mutant lacking the C-terminal 40 amino acids (UvrDΔ40C). However, biochemical findings performed using UvrDΔ40C indicated that this mutant failed to dimerize, although its DNA-unwinding activity was comparable to that of wild-type UvrD. Although the C-terminus plays essential roles in nucleic acid binding for many proteins with helicase and dimerization activities, the exact function of the C-terminus is poorly understood. Thus, to understand the function of the C-terminal amino acids of UvrD, we performed single-molecule direct visualization. Photobleaching of dye-labeled UvrDΔ40C molecules revealed that two or three UvrDΔ40C molecules could bind simultaneously to an 18-bp double-stranded DNA with a 20-nucleotide, 3′ single-stranded DNA tail in the absence of ATP. Simultaneous visualization of association/dissociation of the mutant with/from DNA and the DNA-unwinding dynamics of the mutant in the presence of ATP demonstrated that, as with wild-type UvrD, two or three UvrDΔ40C molecules were primarily responsible for DNA unwinding. The determined association/dissociation rate constants for the second bound monomer were ∼2.5-fold larger than that of wild-type UvrD. The involvement of multiple UvrDΔ40C molecules in DNA unwinding was also observed under a physiological salt concentration (200 mM NaCl). These results suggest that multiple UvrDΔ40C molecules, which may form an oligomer, play an active role in DNA unwinding in vivo and that deleting the C-terminal 40 residues altered the interaction of the second UvrD monomer with DNA without affecting the interaction with the first bound UvrD monomer.